Ultrasound elastography for biomedical applications and medicine. (2018) - Nenadic, Ivan Z (Ivan Zdenko), 1983-; Urban, Matthew W; Gennisson, Jean-Luc; Bernal, Miguel; Tanter, Mikael; Greenleaf, James F
No abstract available